Internalization of Character Values in Learning ‘ILM AL-AṢWĀT - Chairani Astina; Rifqi Aulia Rahman (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2019)
This study aims to identify items of character values ​​and methods of their internalization in learning ‘ilm al-aṣwāt in the Arabic Education Department of UNSIQ Wonosobo. It is a qualitative-descriptive study where data collection is done through observation, interviews, and documentation from the lecturer of ‘ilm al-aṣwāt, lecturer of character education, head of sub-section of academic and student affairs, and some students from semesters 3 and 5 who have taken the course. Participants of this research include the first semester students. Findings of this study show that there are some character values ​​ internalized in students when learning ‘ilm al-aṣwāt. The values ​​are classified into two categories. The first is those that are ​​implied in the learning method such as self-confidence, responsibility, reading interest, achievement-motivated quality, and curiosity. The second is those ​​that are implied in the teaching material of ‘ilm al-aṣwāt such as honesty, self-discipline, communicative attitude, and religiosity. Meanwhile, the internalization itself is done by role-modeling, prioritizing, and reflection.